Community-Acquired Methicillin Resistant Staphylococcus aureus Bacteremia: Case Series - Veni, E JK; Bhat, G; Shalini, SM; Kumar, P; Chakrapani, M; Baliga, S (Kathmandu University Medical Journal, 2015)
Community-acquired methicillin resistant Staphylococcus aureus (MRSA) usually causes skin and soft tissue infections. However, community-acquired methicillin resistant S.aureus has been identified as a causative agent of many invasive infections like necrotizing fasciitis, pneumonia and bacteremia. Risk factors such as immunodeficiency and skin and soft tissue infections have been identified for acquiring bacteremia. We present four cases of bacteremia caused by community-acquired methicillin resistant S.aureus, risk factors and outcome. Kathmandu University Medical Journal Vol.13(1) 2015; 77-79